The Effectiveness of Three Irrigation Systems in the Enterococcus faecalis Reduction after Instrumentation with a Reciprocating Instrument - Fernandes, Karina Gonzalez Camara; Silva, Bruno Barciela da; Boer, Nilton César; Mandarini, Danilo Rodrigues; Moreti, Lucieni Cristina Trovati; Kato, Augusto Shoji; Bueno, Carlos Eduardo da Silveira; Limoeiro, Ana Grasiela da Silva; Pinheiro, Sergio Luiz; Martin, Alexandre Sigrist De; Fontana, Carlos Eduardo (European Journal of Dentistry, 2020)
Objective This study aimed to analyze the effectiveness of three irrigation systems: EndoActivator, passive ultrasonic irrigation (PUI), and Easy Clean in the reduction of Enterococcus faecalis, after instrumentation with the reciprocating system, through microbiological collection and culture method.Materials and Methods A total of 60 extracted human lower premolars were used and standardized at 16 mm in length. The teeth were accessed, contaminated with E. faecalis, and incubated for 21 days at 37°C. Initial collections (S1) were made with an absorbent paper cone to confirm the contamination; subsequently, instrumentation was performed with WaveOne Primary. The teeth were divided into four groups according to the final irrigation protocol (n = 15): group 1. EndoActivator; group 2, PUI; group 3, Easy Clean; and group 4, control group irrigated with saline solution sterile and without agitation. In the final irrigation, the agitation of the 17% ethylene amine tetra-acetic acid (EDTA) solutions was used, then 2.5% sodium hypochlorite (NaOCl); in both for this, three cycles of 20 seconds each. After the chemical–mechanical preparation and agitation of the irrigating solutions, the final collections (S2) for counting the colony-forming units (CFU/mL) occurred.Results The Kruskal–Wallis test revealed that all the agitation systems reduced by 100% and the control group by 65.7%.Conclusion The control group presented a significantly higher amount of CFU/mL after the chemical–mechanical preparation than the other groups, which were similar to each other (p > 0.05).
Keywords: endodontics; EndoActivator; Easy Clean; Enterococcus faecalis; PUI